First Time Isolation of Mycobacterium hassiacum From a Respiratory Sample. Issue 12 (2nd January 2018) - Deinhardt-Emmer, Stefanie; Höring, Steffen; Mura, Christian; Hillemann, Doris; Hermann, Beate; Sachse, Svea; Bohnert, Jürgen; Löffler, Bettina
We describe the first isolation of Mycobacterium hassiacum, a rapid-growing, partial acid-resistant mycobacterium, in a respiratory specimen from a patient with exacerbated chronic obstructive pulmonary disease. To provide therapeutic recommendation for future cases, antibiotic susceptibility testing of 3 clinical isolates was performed by broth microdilution. All strains tested showed susceptibility to clarithromycin, imipenem, ciprofloxacin, and doxycycline. The role of M hassiacum as a respiratory pathogen remains unclear and needs to be evaluated by future reports.